Investigation of Steam Explosion Pretreatment of Sawdust and Oat Straw to Improve Their Quality as Biofuel Pellets - Chukwuka Onyenwoke; Lope G. Tabil; Tim Dumonceaux; Duncan Cree; Edmund Mupondwa; Phani Adapa; Chithra Karunakaran (Energies, 2022)
Steam explosion pretreatment of sawdust and oat straw under mild, medium, and severe conditions was conducted to improve the quality of pellets generated from these feedstocks. This work examined the effects of temperature, time, and moisture content on the mechanical properties of biomass pellets. From the ANOVA conducted, the p-values of the regression models for all the response variables (dimensional stability, tensile strength, and pellet density) studied were significant (p < 0.05), except for the pellet density of steam-pretreated oat straw pellets. The interaction of these three factors did not significantly affect the response variables of oat straw pellets. In addition, the higher heating value (HHV) of treated biomass increased up to a maximum of about 9.5% and 7% as compared with the non-treated sawdust and oat straw, respectively. In addition, an increment of about 3.6-fold and 3.1-fold in pellet tensile strength of steam-pretreated sawdust and oat straw was observed, respectively. Microstructural examination of the pellets from steam-pretreated biomass revealed that the material contained particles that were more closely bonded and featured a cemented surface with fewer pores when compared to particles from untreated oat straw and sawdust.